Zdolności językowe w świetle modularnej teorii umysłu – implikacje glottodydaktyczne - Sadownik, Barbara (Neofilolog, 2019)
The article is devoted to the problem of the nature and structure of the human language capacity. The author addresses the fundamental questions of the place and role language plays among other cognitive faculties, such as perception, thinking, memory, attitude, etc. She first emphasizes the multi-disciplinary character to the research programs dealing with specific and unique attributes of human cognitive system, its structure and function. Current models of the human mind happen to be typically based on diver-gent methodological, epistemological, and ontological assumptions. How useful they prove to be in the end comes with their heuristic value, which is how much inspiration they bring about theoretically as well empirically. It is modular models of the mind that the author subjects to scrutiny and claims to be the basis for further methodological discussion on human capacity for language placed in the context of mono-, bi-, and multilingualism. What makes the author opt for modular conceptions in particular is their theoret-ical relevance, originality, and convergence with latest findings in cognitive neuroscience. The latter is the reason why she takes the cognitive and the neurobiological aspects of language capacity to be complementary to each other. Any and all attempts at relating cognitive neuroscience to modularity theories are, then, said to be interesting and have practical implications. So do neurolinguistic experiments and models of the mind that stem from both neurobiological and modular considerations.